Curriculum Transformation: Integrating Deep Learning to Improve Students' Abilities - Ali, Ridwan (ISTIFHAM, 2025)
Educational transformation in the digital era requires integrating the deep learning approach based on artificial intelligence with traditional humanistic educational values. This study aims to analyze how these two approaches can be synchronized in an effective, adaptive, and holistic curriculum design. A curriculum combining technological aspects with a traditional approach is expected to comprehensively develop students' academic potential and character. On the other hand, the role of teachers in an increasingly digitalized learning ecosystem must also be reconstructed so that they function not only as teachers but also as facilitators, innovators, and curators of knowledge. This study uses a qualitative approach with a literature study, analyzing relevant literature on integrating technology in education and the role of teachers in that context. The study results show that synchronization between the deep learning approach and traditional learning requires a curriculum design that is oriented toward mastery of technology and the formation of character values ​​and students' social competence. In addition, strengthening teacher capacity is key to implementing a transformative curriculum based on technology and human values.